2009
DOI: 10.1007/s00330-009-1457-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Doppler ultrasound for the assessment of plaque ulceration in the stenosed carotid bifurcation by detection of distal turbulence intensity: a matched model study

Abstract: The assessment of flow disturbances due to carotid plaque ulceration may provide added diagnostic information to Doppler ultrasound (DUS) of the carotid stenosis, and indicate whether the associated hemodynamics are a potential thromboembolic source. We evaluated the effect of ulceration in a moderately stenosed carotid bifurcation on distal turbulence intensity (TI) measured using clinical DUS in matched anthropomorphic models. Several physiologically relevant ulcer geometries (hemispherical, mushroom-shaped,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…Similarly, an eccentrically 50%-stenosed model demonstrated turbulence intensity values # 20 cm/s, which increased to 25-30 cm/s in the presence of various ulcerations (Wong et al 2009). This suggests that for mildly to moderately stenosed vessels, factors such as ulcerations also may be a significant contributor to flow disturbances but stenosis severity becomes a more dominant factor with increasing disease.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, an eccentrically 50%-stenosed model demonstrated turbulence intensity values # 20 cm/s, which increased to 25-30 cm/s in the presence of various ulcerations (Wong et al 2009). This suggests that for mildly to moderately stenosed vessels, factors such as ulcerations also may be a significant contributor to flow disturbances but stenosis severity becomes a more dominant factor with increasing disease.…”
Section: Discussionmentioning
confidence: 94%
“…Firstly, plaque ulcerations may induce thrombus formation by disturbing the blood flow. In vitro flow experiments with ultrasound showed that the flow downstream from ulcerated, moderate stenotic, carotid plaques was more disturbed than from nonulcerated plaques [24]. Similarly, an experimental slipstream visualization technique showed that the introduction of an ulceration into a stenotic carotid bifurcation produced observable flow disturbances [4].…”
Section: Discussionmentioning
confidence: 99%
“…30 Flow patterns were visualized by randomly seeding 250,000 tracer particles within and away from the ulcer and tracking their evolution over 3 cardiac cycles, using previously reported techniques.…”
Section: Computational Fluid Dynamicsmentioning
confidence: 99%